Czech Republic : Report on the Observance of Standards and Codes-Banking Supervision-Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The Czech government placed high priority on implementing and observing the international standards relevant for financial stability. The supervisory staff exhibited a high understanding of best international supervisory standards, policies, and practices. Nevertheless, the report noted significant weaknesses in laws governing debtor-creditor relations, inefficiencies in the judicial process, cumbersome administrative requirements, and low supervisory skills, and the need to audit computer-based systems and evaluate risk management systems. Enhancing the legal and regulatory framework is required to build up supervisory capacity, and to increase attention to supervisory coordination and cooperation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CNB Report; CR; ISCR; Risk Management Management System; Risk Management; Czech Republic